Didactics of Geology in Slovakia — History, Current Status and Perspectives - Turanová, Lídia; Ružek, Ivan (Scientia in educatione, 2015)
The didactics of geology as an independent science discipline does not have long history in Slovakia. Its bases and history up to the end of 1992 were common with the Czech Republic. The article deals with the didactics of geology and the role of geology in education at primary and secondary schools in Slovakia. Presented activities for undergraduate and lifelong teacher education play an important role in the improvement of the teaching of geology at schools. The lifelong learning is mainly provided within various projects. The final part of the article analyses and evaluates the current state of geology (geological curriculum) within the framework of state and school education programmes.